Reaction time aspects of elite sprinters in athletic world championships - Tonnessen, E.; Haugen, T.; Shalfawi, S. A. I. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to quantify world-class sprinters' reaction times as a function of performance level, gender, body height, finalists' heat round development, and age. A database of 100-m sprint results and corresponding reaction times from 1,319 sprinters participating in different International Association of Athletics Federations world championships during the time period 2003-9 was compiled for this investigation. Seiko was the official timekeeper of the world championships in this study. Seiko uses a silent gun system for time initiation and false start detection. Their Slit Video system captures the runners at the finish line up to 2,000 images per second with high-resolution cameras. Our results indicate that there was a significant relationship (p < 0.01) between reaction time and 100 m running time, with a shared variance of 8.5 and 10.8% for males (r = 0.292) and females (r = 0.328), respectively. Reaction times (0.166 ± 0.030 seconds) of males were significantly shorter (p < 0.01) than those for females (0.176 ± 0.034 seconds). No relationship was observed between reaction time and height. Male finalist sprinters had substantially shorter reaction times in the finals (0.142 ± 0.017 seconds) compared with round 1 (0.161 ± 0.024 seconds), round 2 (0.155 ± 0.020 seconds), and the semifinals (0.153 ± 0.022 seconds). Female finalist sprinters obtained their fastest reaction times during the semifinals (0.153 ± 0.018 seconds). The best reaction times were registered at the age of 26-29 years for males (0.150 ± 0.017 seconds) and >30 years for females (0.153 ± 0.020 seconds), but reaction times across different age categories were also positively correlated with 100 m performance (p < 0.05). Considering the findings of this study, the results suggest that sprinters' reacting abilities affect their sprint performance over 100 m. This study provides magnitude estimates for the influence of performance level, gender, body height, finalists' heat round, and age on reaction time among world-class sprinters, which we believe to be of great interest for coaches and athletes in sports involving reacting skills.